Critical Clearing Time Analysis of the South Sulawesi Interconnection System Due to Injection of the Sidrap & Jeneponto Wind Turbine - Indar Chaerah Gunadin, Shania Miranda Polopadang, Zaenab Muslimin, Gassing, Agus Siswanto, Muhammad Said (International Journal of Advanced Science and Technology, 2020)
The high demand for electricity causes the need to build more power plants for electricity generation. Because the construction of power plant cannot keep up with the rapid growth of existing loads, then the continuity of the distribution of electrical energy to consumers can be disrupted, which causes the stability of the power system to become unbalanced especially in the stability of the rotor angle. One of the efforts to utilize renewable energy is the construction of a Wind Turbine Power Station (WTPS) in South Sulawesi, namely in the districts of Sidrap and Jeneponto. The method used in analyzing the integration of Sidrap & Jeneponto Wind Turbine is the analysis method by providing 3 phase short circuit interference on the transmission line. The research objective is to determine the stability of the rotor angle and critical clearing time before and after the integration of the Sidrap & Jeneponto Wind Turbine on the Sulselrabar interconnection system using Tools PSAT software. When one of the Sidrap & Jeneponto Wind Turbine is integrated into the rotor angle value system it is still in a stable condition because it is still within the limits that are not beyond 90. When a 3 phase short circuit interruption occurs after the integrated Sidrap & Jeneponto Wind Turbine can further slowdown the generator experiencing synchronous loss with Critical Clearing Time (CCT) when there is a disturbance in the Sungguminasa - Maros CCT transmission line before one of the integrated Wind Turbine in the system is obtained CCT = 0.121 seconds after the integrated Jeneponto Wind Turbine is obtained CCT = 0.125 seconds after the Integrated Sidrap Wind Turbine is obtained CCT = 0.123 seconds.